Open In App

Class 10 NCERT Solutions- Chapter 2 Polynomials – Exercise 2.1

Last Updated : 28 Dec, 2020
Improve
Improve
Like Article
Like
Save
Share
Report

Question 1. The graphs of y = p(x) are given in Fig. 2.10 below, for some polynomials p(x). Find the number of zeroes of p(x), in each case.

Solution:

So, we have equation y = p(x). When p(x) = 0, y = 0. 

That means we only need to find the number of times we get y = 0 in the graph.

In other words, the number of times the graph intersects the x-axis is the answer.

(i) 0. Because the graph doesn’t intersect the x-axis.

(ii) 1. Because the graph intersects the x-axis only at one point.

(iii) 3. Because the graph intersects the x-axis at three points.

(iv) 2. Because the graph intersects the x-axis at two points.

(v) 4. Because the graph intersects the x-axis at four points.

(vi) 3. Because the graph intersects the x-axis at three points.


Previous Article
Next Article

Similar Reads

Class 9 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.1
Question 1. Which of the following expressions are polynomials in one variable and which are not? State reasons for your answer. (i) 4x2 - 3x + 7(ii) y2 + √2(iii) 3√t + t√2(iv) y + 2/y(v) x10 + y3 + t50 Solution: (i) The algebraic expression 4x2 - 3x + 7 can be written as 4x2 - 3x + 7x0 As we can see, all exponents of x are whole numbers, So, the g
4 min read
Class 10 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.2
Question 1. Find the zeroes of the following quadratic polynomials and verify the relationship between the zeroes and the coefficients. (i) x2 – 2x – 8 x2 – 2x – 8 = x2 – 4x + 2x – 8 = x (x – 4) + 2(x – 4) = (x - 4) (x + 2) Therefore, zeroes of equation x2 – 2x – 8 are (4, -2) Sum of zeroes is equal to [4 – 2]= 2 = -(-2)/1 i.e. = -(Coefficient of x
6 min read
Class 9 NCERT Solutions- Chapter 2 Polynomials - Exercise 2.2
Question 1: Find the value of the polynomial (x) = 5x − 4x2 + 3 (i) x = 0 (ii) x = –1 (iii) x = 2 Solution: Given equation: 5x − 4x2 + 3 Therefore, let f(x) = 5x - 4x2 + 3 (i) When x = 0 f(0) = 5(0)-4(0)2+3 = 3 (ii) When x = -1 f(x) = 5x−4x2+3 f(−1) = 5(−1)−4(−1)2+3 = −5–4+3 = −6 (iii) When x = 2 f(x) = 5x−4x2+3 f(2) = 5(2)−4(2)2+3 = 10–16+3 = −3 Q
6 min read
NCERT Solutions Class 9 – Chapter 2 Polynomials – Exercise 2.4
Question 1. Use suitable identities to find the following products:(i) (x + 4) (x + 10) Solution: Using formula, (x + a) (x + b) = x2 + (a + b)x + ab [So, a = 4 and b = 10] (x + 4) (x + 10) = x2 + (4 + 10)x + (4 × 10) = x2 + 14x + 40 (ii) (x + 8) (x - 10) Solution: Using formula, (x + a) (x + b) = x2 + (a + b)x + ab [So, a = 8 and b = −10] (x + 8)
16 min read
NCERT Solutions Class 9 – Chapter 2 Polynomials – Exercise 2.3
Question 1. Determine which of the following polynomials has (x + 1) as a factor:(i) x3+x2+x+1 Solution: p(x) = x3 + x2 + x + 1  Let x+1 be the factor of p(x)Then x = -1 will be the zero of p(x)value of p(-1) should be 0Checking,=> p(-1) = (-1)3 + (-1)2 + (-1) + 1=> -1 + 1 -1 + 1=> 0As p(-1)=0 so (x + 1) is a factor of p(x).  (ii) x4+x3+x2
8 min read
Class 9 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.3
Question 1. Find the remainder when x3 + 3x2 + 3x + 1 is divided by (i) x + 1 Solution: x + 1 = 0 x = −1 Therefore remainder will be f(x): f(−1) = (−1)3 + 3(−1)2 + 3(−1) + 1 = −1 + 3 − 3 + 1 = 0 (ii) x – 1/2 Solution: x - 1/2 = 0 x = 1/2 Therefore remainder will be f(x): f(1/2) = (1/2)3 + 3(1/2)2 + 3(1/2) + 1 = (1/8) + (3/4) + (3/2) + 1 = 27/8 (iii
2 min read
Class 9 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.4
Question 1. Determine which of the following polynomials has (x + 1) as a factor: (i) x3+x2+x+1 Solution: p(x) = x3 + x2 + x + 1 Let x+1 be the factor of p(x)Then x = -1 will be the zero of p(x)value of p(-1) should be 0Checking,=> p(-1) = (-1)3 + (-1)2 + (-1) + 1=> -1 + 1 -1 + 1=> 0As p(-1)=0 so (x + 1) is a factor of p(x). (ii) x4+x3+x2+
9 min read
Class 9 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.5 | Set 2
Chapter 2 Polynomials - Exercise 2.5 | Set 1 Question 9. Verify: (i) x3 + y3 = (x + y) (x2 - xy + y2) Solution: Formula (x + y)3 = x3 + y3 + 3xy(x + y) x3 + y3 = (x + y)3 - 3xy(x + y) x3 + y3 = (x + y) [(x + y)2 - 3xy] x3 + y3 = (x + y) [(x2 + y2 + 2xy) - 3xy] Therefore, x3 + y3 = (x + y) (x2 + y2 - xy) (ii) x3 - y3 = (x - y) (x2 + xy + y2) Solutio
6 min read
Class 9 NCERT Solutions - Chapter 2 Polynomials - Exercise 2.5 | Set 1
Question 1. Use suitable identities to find the following products: (i) (x + 4) (x + 10) Solution: Using formula, (x + a) (x + b) = x2 + (a + b)x + ab [So, a = 4 and b = 10] (x + 4) (x + 10) = x2 + (4 + 10)x + (4 × 10) = x2 + 14x + 40 (ii) (x + 8) (x - 10) Solution: Using formula, (x + a) (x + b) = x2 + (a + b)x + ab [So, a = 8 and b = −10] (x + 8)
11 min read
Class 10 NCERT Solutions- Chapter 2 Polynomials - Exercise 2.3
Question 1. Divide the polynomial p(x) by the polynomial g(x) and find the quotient and remainder in each of the following: (i) p(x) = x3 – 3x2 + 5x – 3, g(x) = x2 – 2 (ii) p(x) = x4 – 3x2 + 4x + 5, g(x) = x2 + 1 – x (iii) p(x) = x4– 5x + 6, g(x) = 2 – x2 Solution: i) p(x) = x3 – 3x2 + 5x – 3, g(x) = x2 – 2 R = 7x-9 Q = x-3 ii) p(x) = x4 – 3x2 + 4x
3 min read